Maqāṣid Al-Sharī‘Ah as the Basis for Reforming Islamic Family Law Legislation: A Comparative Study of Indonesia and Brunei Darussalam - Marzuki, Marzuki; Abdun Nasir, Mohamad; Arifin Haji Munir, Zainal (JURNAL AKTA, 2026)
This article analyzes maqāṣid al-sharī‘ah as a basis for reforming Islamic family law through a comparative study of Indonesia and Brunei Darussalam. The study begins with three main questions: how the principles of ḥifẓ al-dīn, al-nafs, al-‘aql, al-nasl, and al-māl serve as foundations for family law reform; the extent to which these principles are implemented in legislative policies and judicial practices; and how the differing legal-political frameworks of the two countries influence the effectiveness of maqāṣid application. This research employs a normative-comparative legal method with statutory, conceptual, and policy-analysis approaches. The findings show that Indonesia adopts an adaptive reform model through the integration of Islamic law into the national legal system, whereas Brunei implements a more normative and centralized model of sharī‘ah codification. The novelty of this study lies in utilizing maqāṣid as an evaluative instrument for family law politics, rather than merely as an ethical doctrine. The article concludes that maqāṣid al-sharī‘ah can serve as an effective methodological tool for formulating family laws that are responsive and oriented toward the protection of fundamental rights.